Phenology and production of blackberry trees in the southern Minas Gerais - Guilherme dos Santos Cruz; Adriano Bortolotti da Silva; Nágla Maria Sampaio de Matos; Paulo Roberto Corrêa Landgraf; Ana Patrícia Alves Leão (Revista Agrogeoambiental)
The objective of this study was to evaluate the phenology, yield and productivity of “Brazos” and “Tupy” blackberry cultivars in the first production cycle in southern Minas Gerais. The experiment was carried out in a property in the municipality of Serrania – Minas Gerais (MG), with a randomized block design, two cultivars (“Brazos” and “Tupy”), 10 blocks and two useful plants per experimental unit. In the harvest of the 2022/23 production cycle, the beginning, end and duration of flowering were recorded, as well as the beginning, end and duration of the harvest. The following productive parameters were evaluated: number of fruits per plant, fresh fruit mass (g), yield (g plant–1) and estimated productivity (kg ha–1). In mid-November, six fruits per plot were randomly selected to obtain physical fruit parameters (mean lengths and diameters). The data was submitted to analyses of variance and the means were compared using the Tukey test, at 5 % probability. The “Brazos” cultivar had longer flowering and harvest duration. “Tupy” overtook “Brazos” in number of fruits per plant, yield and estimated productivity (p<0.05). “Brazos” produced heavier fruits with a larger diameter (p<0.05). It was concluded that the flowering and harvest duration of the “Brazos” and “Tupy” blackberry cultivars are similar in the first production cycle. During the first production cycle, the “Tupy” cultivar achieved higher production and higher estimated productivity, and the “Brazos” cultivar produced heavier fruits with a larger diameter.